The Effect of Self-Regulated Digital Learning on Learning Outcomes in Islamic Religious Education: The Mediating Role of Learning Motivation at MAS Nurul Fadhilah Deli Serdang - Muhammad Alfah Rizi; Nirzal Sunardi (CV. Zamron Pressindo, 2025)
Research Objective – his study aimed to examine the effect of self-regulated digital learning (SRDL) on learning outcomes in Islamic Religious Education (IRE), with learning motivation as a mediating variable, at MAS Nurul Fadhilah, Percut Sei Tuan, Deli Serdang. The research addresses the gap in empirical studies on digital self-regulated learning within Islamic secondary education, particularly in semi-urban madrasah contexts. Methodology – A quantitative explanatory design with a cross-sectional approach was employed. The study involved 46 students from IRE classes, selected through total sampling. Data were collected using structured questionnaires measuring SRDL and learning motivation, while learning outcomes were obtained from curriculum-based achievement scores. Mediation analysis was conducted using SPSS and Process Macro (Model 4) with 5,000 bootstrap resamples to test indirect effects. Findings – The results indicate that SRDL has a significant positive effect on learning outcomes both directly (β = 0.26, p < 0.05) and indirectly through learning motivation (β = 0.24, 95% CI [0.09, 0.42]), confirming partial mediation. Students who actively regulate their learning in digital environments exhibit higher motivation, engagement, and academic performance in IRE. Research Implications/Limitations – The study highlights the importance of integrating SRDL and motivational strategies in digital PAI instruction. Limitations include the small sample size and the focus on a single madrasah, which may affect generalizability. Originality/Value – This study contributes to the literature by demonstrating the mediating role of learning motivation in linking SRDL to academic outcomes in Islamic education, offering insights for designing learner-centered, motivationally supportive digital learning environments.